2012
DOI: 10.1111/j.1365-2028.2012.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal diet and prey selection of black‐backed jackals on a small‐livestock farm inSouthAfrica

Abstract: The extent to which black‐backed jackals (Canis mesomelas) selectively consume domestic sheep (Ovis aries) compared to wild prey is unknown. Using faecal analysis and prey surveys, we determined the seasonal diet and prey selection of jackals on a small‐livestock farm in South Africa. Sheep comprised 25–48% of the biomass consumed by jackals across seasons, and consumption peaked during the lambing seasons, indicating sheep often were the main food resource for jackals. Another main food resource was wild ungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…On farmland, jackals fed predominantly on small livestock (RFO: 41.6%), especially sheep (RFO: 25.4%). This result is similar to other studies recording livestock feeding in jackals, with RFO ranging from 3.4% to 48.1% with a mean of 21.6% (Grafton , Bothma , Rowe‐Rowe , Kok and Nel , Kamler et al ). Scat analysis cannot confirm if a prey item was actively hunted or scavenged.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…On farmland, jackals fed predominantly on small livestock (RFO: 41.6%), especially sheep (RFO: 25.4%). This result is similar to other studies recording livestock feeding in jackals, with RFO ranging from 3.4% to 48.1% with a mean of 21.6% (Grafton , Bothma , Rowe‐Rowe , Kok and Nel , Kamler et al ). Scat analysis cannot confirm if a prey item was actively hunted or scavenged.…”
Section: Discussionsupporting
confidence: 91%
“…The model converts the dry mass of the undigested remnants of prey in the scats into the biomass ingested of the different prey species. The prey spectrum used by Goszczyński () is similar to that of jackals in our study sites and the model was used by Kamler et al () for jackals. For felids, we used the model recently developed for obligate carnivores by Chakrabarti et al (): Y = (0.033–0.025 exp (−4.284( X / PBM ))) × PBM , where Y is the mass of prey consumed per collectable scat, X is the prey body mass, and PBM is the predator body mass.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both species alter their diets in relation to fluctuations in food availability (Kaunda & Skinner 2003;Maude & Mills 2005;Klare et al 2010;Kamleret al2012), andithas been suggested that in the absence of large predators jackals occupy the niche of apex predators and prey more frequently on large (>15 kg) herbivores (Kamleret al 2010;Klare et al2010;Kamler et al 2012). Both jackal and brown hyaena have also been recorded as occasionally being killed by apex predators (Skinner & Chimimba, 2005;Mills, 1990).…”
Section: Introductionmentioning
confidence: 99%